2020
DOI: 10.1002/cam4.3006
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated hsa_circ_0077837 and hsa_circ_0004826, facilitate bladder cancer progression and predict poor prognosis for bladder cancer patients

Abstract: Growing evidence has indicated that circular RNAs (circRNAs) play crucial roles in multiple biological processes. However, alterations in circRNA profiles during bladder cancer progression and the clinical significance thereof remain unclear.Therefore, high-throughput RNA sequencing was conducted to identify circRNA and mRNA profiles in five pairs of bladder cancer tissues and adjacent noncancerous tissues. A total of 87 differentially expressed circRNAs and 2756 mRNAs were detected in above bladder cancer sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 65 publications
3
27
0
Order By: Relevance
“…Of them, through dual-luciferase reporter assay, hsa_circ_0026782 has been verified that it directly targets miR-874. In accordance with these results, Shen et al (2020) also reported that miR-874-3p was the predicted MREs for hsa_circ_0026782, which confirms the accuracy of our results. In addition, several miRNAs in ceRNA network were reported previously to be involved in the cell cycle, angiogenesis, mucosal fibrosis, and so on.…”
Section: Discussionsupporting
confidence: 92%
“…Of them, through dual-luciferase reporter assay, hsa_circ_0026782 has been verified that it directly targets miR-874. In accordance with these results, Shen et al (2020) also reported that miR-874-3p was the predicted MREs for hsa_circ_0026782, which confirms the accuracy of our results. In addition, several miRNAs in ceRNA network were reported previously to be involved in the cell cycle, angiogenesis, mucosal fibrosis, and so on.…”
Section: Discussionsupporting
confidence: 92%
“…CircEPB41L2 has been previously reported to be down-regulated in human lung adenocarcinoma and bladder cancer, and could predict poor prognosis for patients. 24 , 25 In this study, we also found that the downregulation of circEPB41L2 expression in HCC tissues could promote cell proliferation and metastasis, and thus was significantly correlated with worse RFS time and OS time for HCC patients. Taken together, those results suggested that circEPB41L2 might function as a suppressor role in many solid tumors, including HCC.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, patients with ccRCC and a high level of circ_0085576 had a poor OS and DFS rate; circ_0085576 is derived from the ArfGAP with SH3 domain ankyrin repeat and PH domain 1 gene ( 67 ). By contrast, circ_0004826 and circ_0077837, which are spliced from the utrophin and erythrocyte membrane protein band 4.1-like 2 genes, respectively, are usually expressed at a low level in BC, inhibit tumor cell development and act as a biomarker for OS and RFS in patients with BC ( Table II ) ( 68 ). circRNAs can also act as biomarkers for the effect of drug treatment.…”
Section: Circrnas Act As Biomarkers For the Diagnosis And Prognosis Omentioning
confidence: 99%